Association between surgical volume and failure of primary total hip replacement in England and Wales: findings from a prospective national joint replacement register. Issue 9 (14th September 2020) - Sayers, Adrian; Steele, Fiona; Whitehouse, Michael R; Price, Andrew; Ben-Shlomo, Yoav; Blom, Ashley W
Abstract : Objective: To investigate the association of volume of total hip arthroplasty (THA) between consultants and within the same consultant in the previous year and the hazard of revision using multilevel survival models. Design: Prospective cohort study using data from a national joint replacement register. Setting: Elective THA across all private and public centres in England and Wales between April 2003 and February 2017. Participants: Patients aged 50 years or more undergoing THA for osteoarthritis. Intervention: The volume of THA conducted in the preceding 365 days to the index procedure. Main outcome and measure: Revision surgery (excision, addition or replacement) of a primary THA. Results: Of the 579 858 patients undergoing primary THA (mean baseline age 69.8 years (SD 10.2)), 61.1% were women. Multilevel survival found differing results for between and within-consultant effects. There was a strong volume–revision association between consultants, with a near-linear 43.3% (95% CI 29.1% to 57.4%) reduction of the risk of revision comparing consultants with volumes between 1 and 200 procedures annually. Changes in individual surgeons (within-consultant) case volume showed no evidence of an association with revision. Conclusion: Separation of between-consultant and within-consultant effects of surgical volume reveals how volume contributes to the risk of revision after THA. The lack of association within-consultants suggests that individual changes to consultant volume alone will have little effect on outcomes following THA. These novel findings provide strong evidence supporting the practice of specialisation of hip arthroplasty. It does not support the practice of low-volume consultants increasing their personal volume as it is unlikely their results would improve if this is the only change. Limiting the exposure of patients to consultants with low volumes of THA and greater utilisation of centres with higher volume surgeons with better outcomes may be beneficial to patients.